ANALISIS WACANA PADA BERITA NONTON FILM SAKINAH, MAHASISWA UIN YOGYAKARTA BERI PUJIAN (ANALISIS MIKROSTRUKTURAL) - Resdianto Permata Raharjo; Maranita Anjarsari (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe 1) the form of cohesion contained in the news Watching Sakinah Movies, UIN Yogyakarta Give Praise Students and 2) describing the forms of coherence contained in the news Watching Sakinah Film, Students of UIN Yogyakarta Give Praise. The subjects used in this study were news of watching Sakinah film, UIN Yogyakarta students giving praise, and the objects used were sentences containing grammatical cohesion, a form of lexical cohesion. The approach used in this study is a qualitative descriptive approach. The data in this study are sentences in the news of Watching Sakinah Movies, This student is a method of literature study. While the method of data analysis in this study is descriptive method analysis method, the method used to analyze and describe cohesion markers and analyze markers of coherence. Test The results of the study show that in the news of watching Sakinah films, UIN Yogyakarta Beri Pujian students have varied markers of cohesion and coherence in the Tebuireng Online news discourse. Cohesion markers were found to reference (3), substitution (1), ellipsis (2), conjunction (3), collocation (1), and markers of coherence found cause-effect relationships (2), relationship coherence suggestions — goals (1), coherence temporal relations (1), and coherence of causal relationships (1).